2008
DOI: 10.1063/1.2912517
|View full text |Cite
|
Sign up to set email alerts
|

Statistical equilibrium of bubble oscillations in dilute bubbly flows

Abstract: The problem of predicting the moments of the distribution of bubble radius in bubbly flows is considered. The particular case where bubble oscillations occur due to a rapid ͑impulsive or step change͒ change in pressure is analyzed, and it is mathematically shown that in this case, inviscid bubble oscillations reach a stationary statistical equilibrium, whereby phase cancellations among bubbles with different sizes lead to time-invariant values of the statistics. It is also shown that at statistical equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…If bubble fission occurs after passage of the shock, the fission damping needs to be included in bubbledynamic modelling (Brennen 2002). Moreover, because polydispersity results in different frequency responses for different-sized bubbles, phase cancellations cause an additional apparent damping of the wave propagation (Smereka 2002;Colonius et al 2008;Ando, Colonius & Brennen 2009;Ando 2010).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…If bubble fission occurs after passage of the shock, the fission damping needs to be included in bubbledynamic modelling (Brennen 2002). Moreover, because polydispersity results in different frequency responses for different-sized bubbles, phase cancellations cause an additional apparent damping of the wave propagation (Smereka 2002;Colonius et al 2008;Ando, Colonius & Brennen 2009;Ando 2010).…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…The phase cancellations can be regarded as apparent damping of the wave propagation in the polydisperse mixture, and the damping mechanism becomes more effective as the bubble size distribution broadens. 13,14 As a result, the size distribution increases the attenuation, as seen in Fig. 2.…”
Section: Using the Size Distributions Inmentioning
confidence: 67%
“…(3) and (4) or Eqs. (13) and (14) and are plotted in Fig. 2 from the phase velocity plot that the present modifications to ␦ and N have negligible impact on V. It is also found that the size distribution tends to smooth the transition in V at the resonant frequency.…”
Section: Validation Of the Modificationmentioning
confidence: 94%
See 1 more Smart Citation
“…1) with the probable size R ref and standard deviation σ: delta function that models monodisperse mixtures. The measured distribution of gas bubble nuclei in water tunnels or seawater is reasonably fit by the lognormal distribution with σ ≈ 0.7 [3,24]. For example, the void fraction is computed as…”
Section: Rrmentioning
confidence: 95%